Loss of SLC45A3 protein (prostein) expression in prostate cancer is associated with SLC45A3‐ERG gene rearrangement and an unfavorable clinical course1. Issue 4 (30th August 2012) - Perner, Sven; Rupp, Niels J.; Braun, Martin; Rubin, Mark A.; Moch, Holger; Dietel, Manfred; Wernert, Nicolas; Jung, Klaus; Stephan, Carsten; Kristiansen, Glen
Abstract The majority of prostate cancer harbors recurrent gene fusions involving ETS transcription factors, most commonly ERG. The second most common 5′ fusion partner after TMPRSS2 is SLC45A3. The aim of our study was to quantify the protein expression of ERG, TMPRSS2 and SLC45A3 in prostate cancer to assess for diagnostic or prognostic utility. Six hundred and forty consecutive prostate cancer cases in tissue microarray format were immunohistochemically analyzed for ERG, TMPRSS2 and SLC45A3 protein. Resultant protein expression data was correlated to the respective gene rearrangement status and clinico‐pathological parameters including PSA follow up times. ERG showed no expression in benign prostate glands. In cancer tissue, ERG protein expression showed a high rate of concordance with an underlying ERG rearrangement (91.5%). SLC45A3 showed a weaker expression in cancer as compared to benign tissue, which was pronounced in cases with SLC45A3‐ERG fusion. Importantly, SLC45A3 down regulation was significantly associated with shorter PSA‐free survival times. In contrast, TMPRSS2 was neither differentially expressed nor did it show a correlation between protein expression and rearrangement status. This study provides first evidence that the expression of SLC45A3 protein is down regulated through SLC45A3‐ERG fusion in prostate cancer. Moreover, these cases may represent a distinct molecular subclass of ERG rearranged prostate cancer with distinct clinical features. This study also confirms that ERG protein expression is predominantly found in prostate carcinomas with ERG gene rearrangement and does not occur in benign glands.